Wykorzystanie Internetu w edukacji i pracy osób niewidomych - Łukanowska, Natalia (Wydawnictwo Naukowe UAM w Poznaniu, 2003)
The article deals with using Internet by the blind in their education (especially - in finding information) and work. By using a computer with appropriate software and hardware the visually impaired user can be given access to standard resources. For example, speech synthesis can read a word-processed file to a blind person without the need to have it translated into Braille. Internet also enables the blind to take part in teleeducation and telework.
Using Internet in the education and the work of the blind